Report and discussion. Review of sheep and goats in Morocco (OAU, 1985)
Paper presented at the expert committee meeting on animal genetic resources in Africa, 1983. Presents a brief review of sheep and goats in Morocco. Data on various sheep breeds, their production and reproductive performance and constraints on productivity included.